2015
DOI: 10.1021/jp511385f
|View full text |Cite
|
Sign up to set email alerts
|

4-Pyridyl-9,9′-spirobifluorenes as Host Materials for Green and Sky-Blue Phosphorescent OLEDs

Abstract: We report herein new pyridine-substituted spirobifluorene (SBF) dyes, i.e., 4-(9,9′-spirobi[fluoren]-4-yl)pyridine (4-4Py-SBF), 3-(9,9′-spirobi[fluoren]-4-yl)pyridine (4-3Py-SBF), and 2-(9,9′-spirobi[fluoren]-4-yl)pyridine (4-2Py-SBF), built on the association of the 4-substituted spirobifluorenyl core and various regioisomers of pyridine. These organic semiconductors possess high triplet energy levels (E T around 2.7 eV) in accordance with their use as hosts for green and sky-blue phosphorescent organic light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 60 publications
5
91
0
7
Order By: Relevance
“…We note that compound c1 reported herein widens the scope of substituted fluorenone isomers as key building blocks for the synthesis of spiro derivatives for organics electronics. [14,[25][26][27] Pd Catalysed cross-coupling (Pd(dba) 2 , PCy 3 , KF, DMF, 130°C) between c1 and phenylboronic acid then gives the 1-phenylfluorenone d1 with a high yield of 85%. Thus, despite a sterically hindered environment, incorporation of pendant substituents in position 1 through Pd Catalysed cross-coupling is an interesting strategy to obtain 1-substituted fluorenone derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that compound c1 reported herein widens the scope of substituted fluorenone isomers as key building blocks for the synthesis of spiro derivatives for organics electronics. [14,[25][26][27] Pd Catalysed cross-coupling (Pd(dba) 2 , PCy 3 , KF, DMF, 130°C) between c1 and phenylboronic acid then gives the 1-phenylfluorenone d1 with a high yield of 85%. Thus, despite a sterically hindered environment, incorporation of pendant substituents in position 1 through Pd Catalysed cross-coupling is an interesting strategy to obtain 1-substituted fluorenone derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in order to obtain a high triplet energy (E T ), key feature in the design of host materials for blue PhOLEDs, which are still the weakest link of this technology, it is mandatory to restrict the π-electrons delocalization within the OSC. This π-conjugation disruption has been successfully investigated with ortho linked SBFs (substitution in position 4) [12][13][14][15][16] and meta linked SBFs (substitution in position 3), [2,[17][18][19][20] leading to high performance blue PhOLEDs. However and despite the recent very high efficiency devices obtained by Jiang et al, [17] and by our groups [15] only few examples of 3-and 4-substituted SBFs have been described to date and more importantly no rational structure-properties relationship studies have been reported on SBF regioisomerism.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] As it is known that the increase of HOMO energy levels through the incorporation of phenylacridine, [36][37][38][39] indoloacridine, [40][41][42] quinolinophenothiazine 43 or quinolinophenoxazine 44 moieties instead of a fluorene core has remarkable consequences on the device performance we wish to report herein the first examples of 4-substituted SBF derivatives incorporating electronrich fragments, namely N-phenylcarbazole in 4-PhCz-SBF and trimethoxyphenyl in 4-Ph(OMe) 3 -SBF, Scheme 1. Through a detailed structure-properties relationship study with the corresponding building blocks, namely 4-phenyl-spirobifluorene (4-Ph-SBF), spirobifluorene (SBF), 1,2,3-trimethoxybenzene (Ph(OMe) 3 ) and N-phenyl-carbazole (N-PhCz), we highlight herein the remarkable influence of the C4-substituent on the electronic properties.…”
Section: Chartmentioning
confidence: 99%
“…34,35 Thus, and despite the π-conjugation disruption between the fluorene and its substituent in C4, it has been shown in these previous works that electron-withdrawing groups such as pyridine isomers or pyrimidine (Chart 1) can selectively decrease the LUMO energy levels (localized on the electron poor moiety and/or on the adjacent fluorene core) keeping nevertheless the HOMO energy level (localized on the SBF core) unaltered. 32,33 However, the opposite strategy, that is increasing the HOMO energy level of 4-substituted SBFs, has to the best of our knowledge never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Extremely pure red, green, and blue luminophores with high electrochemical stability and efficiency are particularly essential for a vivid full-color display in organic light-emitting diodes (OLEDs). To date, OLED materials for red and green emission with high performance have been developed [3][4][5][6][7][8][9][10][11]. However, continuous efforts to enhance stability and efficiency in blue fluorescent materials, which possess relatively low chemical and electrochemical properties, caused by the intrinsic wide band-gap, are still required [12,13].…”
Section: Introductionmentioning
confidence: 99%